Evaluation of IL-29 in Euthyroid Patients with Graves’ Orbitopathy: A Preliminary Study - Bogusz Falkowski; Ewelina Szczepanek-Parulska; Nadia Sawicka-Gutaj; Aleksandra Krygier; Marek Ruchala (Mediators of Inflammation)
Background. The most frequent cause of hyperthyroidism is Graves’ disease (GD). Orbitopathy is the most prevalent and recognizable extrathyroidal manifestation of Graves’ disease with unrevealed pathogenesis. Interleukin 29 (IL-29) is a relatively newly discovered inflammatory cytokine. Thus, the aim of this study was to evaluate the relationship between IL-29 and Graves’ orbitopathy (GO) in euthyroid patients. Methods. Thirty-one euthyroid patients with Graves’ disease and with active GO [clinical activity score CAS≥3/7], seventeen euthyroid patients with GD but without GO, and seventy-two healthy control subjects (CS) matched for age and gender were enrolled in the study. The following parameters were evaluated in every participant: thyroid-related hormones and autoantibodies and inflammatory markers (white blood cells, hsCRP). ELISA assay was applied to measure the concentration of IL-29. Results. We found higher level of IL-29 in GO group in comparison with CS [165 (133-747) vs. 62 (62-217) pg/mL, p<0.001]. Furthermore, participants in the subgroup with GD with GO as compared with GD without GO had higher concentration of IL-29 [165 (133-747) vs. 62 (62-558) pg/mL, p=0.031]. The ROC analysis for IL-29 revealed IL-29 cut-off of 105 pg/mL (sensitivity 1.000 and specificity 0.597) as the best value significantly indicating the presence of GO in GD [area under the ROC curve (AUC): 0.739, 95% confidence interval (CI): 0.646-0.833, p<0.001]. Conclusions. The present study revealed for the first time an elevated level of IL-29 in the serum of patients with GD and GO that might suggest its involvement in the pathogenesis of GD ocular complications.